TEKNIK AUDIT BERBANTUAN KOMPUTER SEBAGAI PREDIKTOR KUALITAS AUDIT - Dewi, IGAA Pradnyani Harum; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 12 No 1 (2015), 2015)
This paper analyzes about Computer Assisted Audit Techniques (TABK) on audit quality. This research was conducted in the BPK RI Representative Bali Province. The data collected in this study with saturated sample method. Data analysis technique in this paper uses simple linear regression. This paper gives the results TABK positive and statistically significant in audit quality, which means that the better the quality the better the application TABK audit.
Keywords: Computer Assisted Audit Techniques (CATTs), audit quality